Analysis of the Fulfilment of the Rights of Women Teachers in Islamic Boarding Schools by Prof. Dr Hamka Maninjau in Terms of Law No. 13 of 2003 - Ridha, Abdurrasyid Ridha; Junaidi, Junaidi; Yakub Simbolon, Ali Mustopa; Ulmadevi, Ulmadevi; Bashori, Bashori (HUMANISMA : Journal of Gender Studies, 2023)
This research aims to analyse the fulfilment of the rights of female teachers in educational institutions based on Law Number 13 of 2003, known as labour law. The goal is to see the extent to which educational institutions step in to understand and implement the law as stipulated by the government. Previous research did not discuss the fulfilment of women's rights in the field of education. The majority of existing research is carried out in companies, so the position of women teachers in the field of education tends to be forgotten. The method used in this research is qualitative research with data collection techniques in the form of observation and interviews. The results found that Prof. Hamka Maninjau Islamic Boarding School has fulfilled the rights of female teachers as well as possible. It can be seen from the form of leave and facilities provided for teachers who still have children who are still breastfeeding.Penilitian ini bertujuan untuk menganalisis pemenuhan hak-hak guru perempuan di lembaga pendidikan berdasarkan Undang-Undang nomor 13 tahun 2003 yang dikenal dengan undang-undang ketenagakerjaan. Tujuannya adalah melihat sejauh mana langkah lembaga pendidikan dalam memahami dan melaksanakan undang-undang tersebut sebagaimana yang telah ditetapkan oleh pemerintah. Penelitian terdahulu tidak banyak membahas mengenai pemenuhan hak pekerja perempuan dibidang pendidikan. penelitian yang ada mayoritas dilaksanakan di perusahaan-perusahaan sehingga posisi guru perempuan di bidang pendidikan cenderung terlupakan. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif dengan teknik pengumpulan data berupa observasi serta wawancara. Hasil yang ditemukan bahwa Pondok Pesantren Prof. Hamka Maninjau telah memenuhi hak-hak guru perembuan dengan sebaik-baiknya. Terlihat dari bentuk cuti dan kemudahan yang diberikan bagi guru yang masih memiliki anak yang masih ASI.